2015
DOI: 10.1155/2015/637853
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and Correlation of iNOS and p53 in Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is the most prevalent form of oral cancer. Inducible nitric oxide synthase (iNOS) and p53 are associated with a variety of human cancers, but their expression and interaction in OSCC have not been fully explored. In this study, we investigated the expression of iNOS and p53 in OSCC and their correlation with tumor development and prognosis. In addition, we explored the interaction of iNOS and p53 in OSCC. The expression of iNOS and p53 in OSCC was investigated using immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 26 publications
6
24
1
3
Order By: Relevance
“…Therefore, elevated NO concentration in tumors selectively kills healthy cells and allows cancer cells to survive, thereby contributing to tumor progression [27]. A correlative study in oral squamous cell carcinoma patients made a similar observation, where tumors in advanced stages of the disease showed higher NOS expression and lower p53 expression [28]. …”
Section: No: Modulator Of the Tmementioning
confidence: 98%
“…Therefore, elevated NO concentration in tumors selectively kills healthy cells and allows cancer cells to survive, thereby contributing to tumor progression [27]. A correlative study in oral squamous cell carcinoma patients made a similar observation, where tumors in advanced stages of the disease showed higher NOS expression and lower p53 expression [28]. …”
Section: No: Modulator Of the Tmementioning
confidence: 98%
“…Carcinogenesis is a multistep process that requires an elusive sequence of genetic, epigenetic, and metabolic changes, which produce deregulations in various intracellular signaling pathways. A large number of activities mediated by iNOS/NO may contribute to tumorigenesis, including the induction of cellular damage, increased angiogenesis, reduction of apoptosis, suppression of the immune system, and NO‐direct mutagenesis . In fact, iNOS can modulate each of the changes in cellular activities that are distinctive and specific to the neoplastic cells, independently of or in combination with other signaling pathways …”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated an ordered increase in iNOS expression from healthy tissue, through epithelial precursor lesions up to OSCC . Others have correlated high levels of iNOS with OSCC locoregional metastasis, angiogenesis, and p53 up‐regulation . Such data suggest an essential role of iNOS in OSCC development and progression.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nitric oxide is a gas and also serves as a neurotransmitter and vasodilator 16 .iNOS over expression has also been observed in squamous cell carcinoma 17 .In the progression of squamous cell carcinomas P53 and iNOS expression is strongly co-related 18 .…”
Section: Introductionmentioning
confidence: 99%